Characteristics of Athletes’ Psychological State before Competition and the Correlation Analysis of the Psychological State of Athletes of Different Levels - Liu Yong (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This article analyzes the mental state data of athletes, and concludes that depression has a strong correlation with mental states such as potential risk of suicide and anxiety. Static features include some basic attributes of athletes, which are related to depression through hypothesis testing and regression analysis. Dynamic features are constructed from the mental state data generated by athletes on the playing field, which can represent athletes’ consumption related to changes in athletes’ behavior. This paper analyzes the principle of the interactive multi-model algorithm in more detail, and solves the problem of the uncertainty of the target athlete's mental state measurement points and the target athlete's mental state. Aiming at the problem of the target athlete’s mental state loss during the evaluation process, the expanded correlation gate is applied to this algorithm. When the target athlete’s mental state is manoeuvring and no effective measurement can be detected in the correlation gate, the correlation gate gradually expands. At the same time, in order to reduce the computational complexity of the new algorithm as much as possible, the pre-defined sampling interval method is used to adaptively adjust the evaluation sampling period to balance the judgment accuracy of the athlete's mental state. The results of the study show that the self-confidence of each athlete representative team is generally higher, which is basically above the average level. Only a few teams have not reached the average level of self-confidence. No difference is found in the self-confidence subscale between men and women's volleyball teams. In the individual failure anxiety subscale, the top three teams are all lower than the overall average, and the individual failure anxiety of other athlete teams is higher. Physical anxiety levels of the top three teams are below the overall average level, and the level of physical anxiety is not high. The fourth to sixth places are all above the average level, and the level of physical anxiety is high. The biggest obstacle for high-level athletes to form an ideal pre-match state is that athletes have a high degree of anxiety about social expectations. All high-level sports teams continue to maintain this high-confidence pre-match mental state, which helps athletes experience a good level of arousal before the game.